Mediolateral oversizing influences pain, function, and flexion after TKA - Bonnin, Michel P. (Springer Berlin Heidelberg, 2013)
PURPOSE: Manufacturers of total knee arthroplasty (TKA) have introduced narrower femurs to improve bone-implant fit. However, few studies have reported the clinical consequences of mediolateral oversizing. Our hypothesis was that component oversizing negatively influences the results after TKA. METHODS: One hundred and twelve prospectively followed patients with 114 consecutive TKA (64 females and 50 males) were retrospectively assessed. The mean age of the patients was 72 years (range, 56 to 85 years). The dimensions of the femur and tibia were measured on a preoperative CT-scan and were compared with those of the implanted TKA. The influence of size variation on the clinical outcomes 1 year after surgery was assessed. RESULTS: Mediolateral overhang was observed in at least one area in 66 % of the femurs (84 % in females and 54 % in males) and 61 % of the tibia (81 % in females and 40 % in males). Twenty-two patients presented no overhang in any area and 16 had overhang in all studied zones. The increase in the Pain and KOOS scores were 43 ± 21 and 36 ± 18 in the patients without overhang and 31 ± 19 and 25 ± 13 in patients with overhang (p = 0.033; p = 0.032). Knee flexion was 127° ± 7 and 121° ± 11, respectively. Regression and latent class analysis showed a significant negative correlation between overall oversizing and overall outcome. CONCLUSIONS: This study confirms that oversizing may lead to worse clinical results in TKA. The clinical consequences are that surgeons should pay attention not to oversize implants during implantation nd that oversizing should be ruled out in case of so called unexplained pain. LEVEL OF EVIDENCE: IV. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00167-013-2443-x) contains supplementary material, which is available to authorized users.